Kant's political theory : interpretations and applications - Ellis, Elisabeth (Pennsylvania State University Press, 2012)
"A collection of essays examining Immanuel Kant's lectures and minor writings as well as his political essays. Offers a comprehensive introduction to Kant's political thought from a position of engagement with modern political and philosophical questions"--Provided by publisher